2018
DOI: 10.1017/s0266462318000478
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assurance of Registries for Health Technology Assessment

Abstract: Objectives:The aim of this study was to identify guidelines and assessment tools used by health technology agencies for quality assurance of registries and investigate the current use of registry data by HTA organizations worldwide.Methods:As part of a European Network for Health Technology Assessment Joint Action work package, we undertook a literature search and sent a questionnaire to all partner organizations on the work package and all organizations listed in the International Society for Pharmaco-economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 10 publications
0
11
0
1
Order By: Relevance
“…An EUnetHTA survey examining the extent to which HTA agencies use sources of RWE such as registries (29) showed that, particularly in Europe, some agencies use clinical and administrative databases, besides clinical registries to gather additional data for HTA. Less than half, however, currently employ criteria for quality checking these data sources, in most cases defined by each organization rather than external bodies with standardized tools.…”
Section: Lessons Learnt and Implications At The National And European Levelsmentioning
confidence: 99%
“…An EUnetHTA survey examining the extent to which HTA agencies use sources of RWE such as registries (29) showed that, particularly in Europe, some agencies use clinical and administrative databases, besides clinical registries to gather additional data for HTA. Less than half, however, currently employ criteria for quality checking these data sources, in most cases defined by each organization rather than external bodies with standardized tools.…”
Section: Lessons Learnt and Implications At The National And European Levelsmentioning
confidence: 99%
“…In other examples, unpublished data were used to provide contextual information (other than effectiveness or harms/safety information), for example, to detail uptake of services, patient characteristics, epidemiology, natural history, or cost or data for cost-effectiveness analyses. [21][22][23][24][25] After completion of the review, the unpublished health system data can be used as a "data appendage" to help filter, interpret, and/or apply the review findings to an individual health system's practice. This may not involve the systematic reviewers themselves and could be performed by the health system using the systematic review.…”
Section: Examples Of Using Health System Data Before During or After Conducting A Systematic Reviewmentioning
confidence: 99%
“…33 Data quality is complex because it touches on multiple dimensions (e.g., data accuracy, data completeness, interpretability and accessibility of data, relevance of the data, timeliness of the data, coherence of the data, and mode of the data collection and how it impacts data quality) and can fluctuate over time and across data sources. 21 The issues centered on data quality are not unique to health system data but may be more problematic depending on the data source being used and the questions being asked.…”
Section: Understanding the Limitations Of Using Unpublished Primary Data From Health Systems In Systematic Reviewsmentioning
confidence: 99%
“…In other examples, unpublished data were used to provide contextual information (other than effectiveness or harms/safety information); for example, to detail uptake of services, patient characteristics, epidemiology, natural history, or cost or data for cost-effectiveness analyses. [19][20][21][22][23] In some instances, the rationale for using unpublished data was not evident and/or appeared opportunistic (i.e., researchers had access to their own unpublished data and included it because it was available), and was not applied to healthcare decision making. Overall the examples we identified applied clinical practice data or specific registry data from a single health system (e.g., Mayo Clinic) or regional or nationally representative data (e.g., clinical registries, hospital database).…”
Section: Inform Strength Application or Implementation Of Evidencementioning
confidence: 99%